The Turkish validity and reliability study of the London measure of unplanned pregnancy - Altiparmak, Sumeyye; Yilmaz, Ayse N.; Aksoy Derya, Yesim (Wiley, 2021)
Aim This study aims to adapt the London Measure of Unplanned Pregnancy (LMUP) developed by Barrett et al. to Turkish by checking its validity and reliability. Method The sample of this methodological study consisted of 596 pregnant women who were referred to the antenatal outpatient clinics of a public hospital in eastern Turkey. Data were collected from those who agreed to participate in the study, by using a personal information form and the six-item LMUP. Data were analyzed using SPSS 25.0 and AMOS 24.0 statistical package programs, and statistically assessed using descriptive statistics such as number, percentage, mean and SD, language and content validity, explanatory factor analysis (EFA), confirmatory factor analysis (CFA), Cronbach's alpha reliability coefficient, and test-retest analysis. Results The EFA revealed that the Turkish version of the LMUP consisted of five items and one factor. The items' factor loadings were above 0.30, and explained 68.89% of the total variance. The CFA supported the one-factor structure of the scale, which was revealed by the EFA. As a result of the CFA, the fit indices were found to be very good. The Cronbach's alpha coefficient of the scale was determined as 0.90. Conclusion The Turkish version of the LMUP is a valid and reliable instrument to evaluate unplanned pregnancy.
Keywords: LMUP; reliability; Turkish version; unplanned pregnancy; validity